Contrast media use in patients with chronic kidney disease undergoing coronary angiography: A systematic review and meta-analysis of randomized trials. (1st February 2017) - Pandya, Bhavi; Chaloub, Jean; Parikh, Valay; Gaddam, Sainath; Spagnola, Jonathan; El-Sayegh, Suzanne; Bogin, Marc; Kandov, Ruben; Lafferty, James; Bangalore, Sripal
Abstract: Background: Patients with chronic kidney disease (CKD) undergoing coronary angiography (CA), adequate hydration and minimizing volume of contrast media (CM) are class 1b recommendations for preventing contrast induced nephropathy (CIN). Current data are insufficient to justify specific recommendations about isoosmolar vs. low-osmolar contrast media by the ACCF/AHA/ SCA I guidelines. Methods: Randomized trials comparing IOCM to LOCM in CKD stage 3 and above patients undergoing CA, and reporting incidence of CIN (defined by a rise in creatinine of 25% from baseline) were included in the analysis. The secondary outcome of the study was the incidence of serum creatinine increase by > 1 mg/dl. Results: A total of 2839 patients were included in 10 trials, in which 1430 patients received IOCM and 1393 received LOCM. When compared to LOCM, IOCM was not associated with significant benefit in preventing CIN (OR = 0.72, [CI: 0.50–1.04], P = 0.08, I2 = 59%). Subgroup analysis revealed non-significant difference in incidence of CIN based on baseline use of N -acetylcystine (NAC), diabetes status, ejection fraction, and whether percutaneous coronary intervention vs coronary angiography alone was performed. The difference between IOCM and LOCM was further attenuated when restricted to studies with larger sample size (> 250 patients) (OR = 0.93; [CI: 0.66–1.30]) or when compared with non-ionic LOCM (OR = 0.79, [CI: 0.52–1.21]). Conclusion: In patients with CKD stage 3 and above undergoing coronary angiography, use of IOCM showed overall non-significant difference in incidence of CIN compared to LOCM. The difference was further attenuated when IOCM was compared with non-ionic LOCM.